Revisiting the Kaleidoscope Model for Policy Analysis and Exploring its Applicability to the Complex Agrifood Systems of Countries in Central and West Asia and North Africa: Methodological Guideline - Dhehibi, Boubaker; M. Oumer, Ali; Frija, Aymen; Akramov, Kamiljon; Baum, Michael (International Center for Agricultural Research in the Dry Areas, 2023)
Policies are critical to improving agrifood systems innovations and overall economic performance. While favorable policy decisions shape the incentives and actions of stakeholders, suboptimal policies could create bottlenecks and hinder development progress (Haggblade and Babu 2017; Resnick et al. 2018). Therefore, having an impact on policy decisions requires a good understanding of a given country’s underlying policy processes. Policies are, however, implemented by a range of stakeholders and bringing them together for action is often a challenge. The Kaleidoscope Model (KM) can be used to analyze policy and institutional constraints and key drivers of agrifood policy change in Central and West Asia and North Africa (CWANA). This research is being implemented by a team of researchers from CGIAR research centers ICARDA, IFPRI, and IWMI and in collaboration with international and national partners across CWANA countries.